The Role of Educational Philosophy in the Formation of a Sustainable Economy in Makassar City - Ibadurrahman Ibadurrahman; Abdullah Sinring; Syamsu A. Kamaruddin; Ambo Paerah; Syamsinar Syamsinar (Edumaspul: Jurnal Pendidikan, 2025)
This study highlights how educational philosophy plays a role in promoting sustainable economic development in Makassar City. This study stems from the need to manage economic growth in a more holistic manner, not only pursuing financial gains but also considering social and environmental aspects. Using a descriptive qualitative approach through case study methods, this research examines how sustainability values are instilled in the community through the education system. Data was collected through in-depth interviews, participatory observation, and review of various relevant documents. The results of the study show that educational philosophy plays a central role in building public awareness and behavior towards sustainable economic practices. Programs such as the Green School in Makassar are concrete evidence of the application of sustainability values in education. However, various obstacles still arise, including a lack of policy support, minimal educational facilities, and low public awareness of the importance of sustainability. Therefore, this study recommends strengthening sustainability-oriented curricula, increasing the capacity of educators, and fostering cooperation between the government, educational institutions, and the community to create an educational ecosystem that promotes a sustainable economy.